2010
DOI: 10.1096/fj.09-152017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal distribution of inositol 1,4,5‐trisphosphate receptors in human muscle can be related to altered calcium signals and gene expression in Duchenne dystrophy‐derived cells

Abstract: Inositol 1,4,5-trisphosphate (IP(3)) receptors (IP(3)Rs) drive calcium signals involved in skeletal muscle excitation-transcription coupling and plasticity; IP(3)R subtype distribution and downstream events evoked by their activation have not been studied in human muscle nor has their possible alteration in Duchenne muscular dystrophy (DMD). We studied the expression and localization of IP(3)R subtypes in normal and DMD human muscle and in normal (RCMH) and dystrophic (RCDMD) human muscle cell lines. In normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…When human muscle was studied, type II muscle fibers showed a much more intense labeling for the IP 3 R subtype 1 compared to type I (slow) fibers. In biopsies from DMD patients, we found that 24 ± 7% of type II fibers have totally lost type 1 IP 3 R labeling, compared to age-matched control biopsies (Cárdenas et al 2010). On the other hand, RCDMD cells show a five-fold over expression of type 2 IP 3 Rs and down regulation of type 3 IP 3 Rs compared to normal RCMH cells (Cárdenas et al 2010).…”
Section: Alterations In Both Ip 3 Rs and E-t Coupling In Dmd Modelsmentioning
confidence: 70%
See 4 more Smart Citations
“…When human muscle was studied, type II muscle fibers showed a much more intense labeling for the IP 3 R subtype 1 compared to type I (slow) fibers. In biopsies from DMD patients, we found that 24 ± 7% of type II fibers have totally lost type 1 IP 3 R labeling, compared to age-matched control biopsies (Cárdenas et al 2010). On the other hand, RCDMD cells show a five-fold over expression of type 2 IP 3 Rs and down regulation of type 3 IP 3 Rs compared to normal RCMH cells (Cárdenas et al 2010).…”
Section: Alterations In Both Ip 3 Rs and E-t Coupling In Dmd Modelsmentioning
confidence: 70%
“…In biopsies from DMD patients, we found that 24 ± 7% of type II fibers have totally lost type 1 IP 3 R labeling, compared to age-matched control biopsies (Cárdenas et al 2010). On the other hand, RCDMD cells show a five-fold over expression of type 2 IP 3 Rs and down regulation of type 3 IP 3 Rs compared to normal RCMH cells (Cárdenas et al 2010). Unlike normal muscle cells, type 2 IP 3 R locate in the nucleus in RCDMD cells, while type 1 and type 3 IP 3 Rs also display a particular subcellular location for each line (Cárdenas et al 2010).…”
Section: Alterations In Both Ip 3 Rs and E-t Coupling In Dmd Modelsmentioning
confidence: 70%
See 3 more Smart Citations